Islamic perspectives relating to business, arts, culture and communication [electronic resource] : Proceedings of the 1st ICIBACC 2014 - Omar, Roaimah; Bahrom, Hasan; de Mello, Geraldine; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This timely book explores how the Malays and Muslims in general are faced with challenges in the fields of business, economy and politics, in the modern era of globalisation. These research findings can help the Muslim community to enhance international integration, particularly in Malaysia and Southeast Asia. In this work, scholarly and expert authors explore Islamic perspectives on communication, art and culture, business, and law and policy. They respond to the need to uphold and strengthen the culture, arts and heritage of the Malays. Readers are invited to explore the challenges for the Malay and Muslim world and to evolve strategies to ensure competitiveness, dynamism and sustainability. Topics such as Islamophobia, drug trafficking, savings behaviours and the role of social media are addressed. These reviewed papers were presented at the International Conference on Islamic Business, Art, Culture & Communication 2014, held in Melaka, Malaysia. They have the potential to strengthen aspects of Islamic economy and leadership, if translated into action plans. This book represents essential reading for scholars of Islamic studies and will be of interest to those examining Southeast Asia and the Malay world.
Part I: Islamic Studies and Communication -- Chapter 1: Development of Ethno-mathematics of Al-Qur?an, Al-Hadith and Jawi Scripts for Computer Security -- Chapter 2: Is an Islamic Scientific Study of Religion Possible? A Preliminary Discourse with Reference to the Muslim Scholarship in Religionswissenschaft -- Chapter 3: Terrorism and Islamophobic: Media Representation on Islam and Middle East -- Chapter 4: Metaphorical Visual Persuasion: The Perception of Malay Products in Press Advertisements -- Chapter 5: Role of Social Media in Disseminating Dakwah -- Part II: Art and Culture -- Chapter 6: A Comparative Study of Brocade Weaving Art Motifs and Designs in Iran and Malaysia -- Chapter 7: Decision to have Children from the Perspective of Young Malay Muslim Academic Women -- Chapter 8: Factors associated with the Adoption of Sexual Abstinence and Contraception among Moshood Abiola Polytechnic Students in Abeokuta, Nigeria -- Chapter 9: ?Light? in Malay Songket. Is it Real? -- Chapter 10: ?Light?: Visible to a Person can be Hidden from Others -- Chapter 11: Linking Neuropolitics to the Politics of Reconciliation in Relation to Political Non-Apology: A Case of Malaysia -- Chapter 12: Marginalised Malay Females: A Socio-demographic Analysis on Female Prisoners in the Malaysian Prisons -- Chapter 13: Structural-Semantic Analysis: A Method towards a Classification of Malaysian Folktale -- Chapter 14: Sustaining Cultural Heritage through Heritage-led Regeneration -- Chapter 15: The Design and Environmental Aspects of the Prayer Room -- Chapter 16: The Effects of Cultural Values on Traditional Islamic-Arabic Houses in the Middle-East -- Chapter 17: The Influence of Foreign and Local Cultures on Traditional Mosques in Indonesia -- Chapter 18: The Influence of Malays? Social Hierarchy in the Implementation of a Western-based Participatory Action Research Project in Malaysia -- Chapter 19: The Perils of Drug Trafficking: Endangering the Malay and Muslim Society -- Chapter 20: The Practice of Modern Family Planning Methods amongst Married Muslim Women in Katsina, Katsina State, Nigeria -- Chapter 21: The Tubau: Symbol of Unity -- Chapter 22: Traditional Craftsmanship: The Origin, Culture and Challenges of Batik Industry in Malaysia -- Chapter 23: Traditional House of Negeri Sembilan: Interior Layout Plan and Relation to Compatibility Islamic Principles and Matrilineal -- Part III: Business -- Chapter 24: Attitude and Perceptions of Malay Muslim Students towards Educational Loan Repayment: A Qualitative Approach -- Chapter 25: Bumiputra Entrepreneurs? Perception and Propensity to Sustainable Entrepreneurship -- Chapter 26: Determinants of Savings Behaviour among Muslims in Malaysia: An Empirical Investigation -- Chapter 27: Financing Higher Education Students in Malaysia using Islamic Student Loan-backed Securitisation: An Empirical Analysis -- Chapter 28: Grievances on Islamic Banks: A Survey -- Chapter 29: How Islamic Banking do Justice to Malaysian Society? -- Chapter 30: Integrating Zakat Institutions into the Mainstream Economy: Evidence from Malaysia -- Chapter 31: Islamic Perspective of Human Talent Identification and Organisational Justice: Evidence from Government-linked Companies in Malaysia -- Chapter 32: Overview of Production and Tendency on Halal Products and Services in Malaysia and Global Market -- Chapter 33: Relationship between Leaders? Role and Lecturers? Innovative Work Behaviour in UiTM Cawangan Melaka -- Chapter 34: Sense of Community among Malay Customers: Evidence from Western Food Outlets in Malaysia using Structural Equation Modeling Approach (SEM) -- Chapter 35: Students? Satisfaction with the University Cafetaria: Structural Relationships of Food Quality, Staff, Price Fairness and Ambiance -- Chapter 36: The Business Web Genre - A Genre Analysis on the Websites of Selected Malaysian Small and Medium Enterprises (SMEs) -- Chapter 37: The Effectiveness of Service Quality by Jabatan Agama Islam Wilayah Persekutuan (Jawi) towards Customer Satisfaction -- Chapter 38: The Performance of Married and Single Mother Entrepreneurs: Evidence from Malaysia -- Chapter 39: Why Brand Equity Matters in Globalised Malay and Islamic Country, Malaysia? -- Part IV: Law and Policy -- Chapter 40: A Survey to Assess the Female Sexual Harassment in the Higher Educational Institutes of Karachi, Pakistan -- Chapter 41: E-Participation among Members of Parliament in Malaysia: Evaluation of Social Factors -- Chapter 42: In the Purview of an Oath from the Jurisprudential Method of Islamic Law of Evidence -- Chapter 43: A Study of Syariah Whipping as Punishment for Drug Dependants in Malaysia.
Keywords: Social sciences; Arts; Finance